Trust: The feature that vending machines and ATMs share, but SimplyGo lacks - LIM, Sun Sun (Institutional Knowledge at Singapore Management University, 2024)
The article discussed the intricacies of trust in the SimplyGo debacle and highlighted how the design of physical interfaces like vending machines and ATMs and digital interfaces from apps like Grab, Parking.sg and ShopBack have critical features to instil trust. People need to be reassured that their transactions have proceeded as they should, and thay have not been short-changed.